Influence of growth stages and harvesting season, and drying methods on phytochemical content and antioxidant activity of Cosmos caudatus kunth leaves - Mediani, Ahmed (2012)
Cosmos caudatus which is locally known as ´´ulam raja, is one of the local Malaysian herbs used traditionally as medicinal herbal in treating several maladies and as a food because of the general confidence of its high antioxidant activity (AA). The main aim of this study was to determine the preferable drying methods, suitable harvesting plant age and best growing season for obtaining valuable C. caudatus products. Optimizing oven drying conditions (e.g. drying time and oven temperature) has been shown to affect AA and total phenolic content (TPC) of this particular herb when the response surface methodology was applied with central composite design (RSM CCD). The assessments of various growth stages (8, 10, and 12 weeks) and season on TPC and AA were also conducted. Meanwhile, the differences among oven-, air- and freeze-dried C. caudatus were determined, and the dried samples were compared with the frozen samples (FS) to evaluate the effects of storage time on its TPC and AA. 1H nuclear magnetic resonance (1H-NMR) combined with principal components analysis (PCA) and partial least-squares discriminate analysis (PLS-DA) was applied to distinguish variations of C. caudatus samples processed with various drying techniques. Results showed that the optimized conditions of oven drying (OD) method for 80% methanol and 80% ethanol extract were 44.5°C for 4 h and 43.12°C for 4.05 h, with IC50 of 0.045 and 0.055 mg/ml, respectively. The predicted values for TPC in optimized conditions for 80 % methanol and 80% ethanol were 16.5 and 15.8 mg GAE/100 g DW, respectively. Eight-week-old herbs harvested at dry season exhibited the highest TPC and the lowest IC50 values. The difference in TPC was shown to be significant (P.0.05) among the drying methods and the three development stages, while AA exhibited considerable changes for the three growth stages studied. Except for oven drying, the difference between freeze- and air- drying was rather insignificant. After 120 days of storage, the dried samples showed a high and consistent AA compared to the frozen material. As for the metabolomics study, PCA and PLS scores revealed noticeable clear separated clusters representing the three drying methods by PC1 and PC2, with an eigenvalue of 77.9%. Various assigned signals that were referring to metabolites responsible for the sample variation were also ascribed. The identified compounds were > glucose, chlorogenic acid, rutin, quercetin, quercetin 3-O-B rhamnoside, quercetin 3-O->-arabinofuranoside and quercetin 3-O-B glucoside. The identification of metabolites was further confirmed through LC-MS/MS profiling and by comparing with NMR spectra of pure compounds. The findings obtained in this study showed that Cosmos caudatus could be used as a potential source of antioxidant, and a versatile herb for medicinal applications.